2021
DOI: 10.1212/nxg.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Brain Regional Differences in Hexanucleotide Repeat Length in X-Linked Dystonia-Parkinsonism Using Nanopore Sequencing

Abstract: ObjectiveOur study investigated the presence of regional differences in hexanucleotide repeat number in postmortem brain tissues of 2 patients with X-linked dystonia-parkinsonism (XDP), a combined dystonia-parkinsonism syndrome modified by a (CCCTCT)n repeat within the causal SINE-VNTR-Alu retrotransposon insertion in the TAF1 gene.MethodsGenomic DNA was extracted from blood and postmortem brain samples, including the basal ganglia and cortex from both patients and from the cerebellum, midbrain, and pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…DNA was extracted with the Blood and Cell Culture DNA Midi kit (Qiagen). Long-range PCR was performed to amplify the TAF1 SVA (amplicon Size: 3.2 kb) in XDP patients, as previously described [ 7 ], using the PrimeSTAR GXL DNA Polymerase ® (Takara Bio). The primer sequences are documented in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted with the Blood and Cell Culture DNA Midi kit (Qiagen). Long-range PCR was performed to amplify the TAF1 SVA (amplicon Size: 3.2 kb) in XDP patients, as previously described [ 7 ], using the PrimeSTAR GXL DNA Polymerase ® (Takara Bio). The primer sequences are documented in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…The repeat number is inversely correlated with age at onset and disease severity [ 5 , 6 ]. In addition, somatic mosaicism has been observed, with a higher median number of repeats detected in the cerebellum and basal ganglia compared to blood [ 7 ]. In XDP patients, seven variants have been found on the X chromosome: five single-nucleotide variants (SNVs), a 48-bp deletion and the SVA insertion [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…All DNA was extracted from the Blood and Cell Culture DNA Midi kit (Qiagen). Sequencing was performed for the SVA amplicon (3.2kb) and Cas9 enrichment as previously described 8 , with super accuracy model for base calling and mapped to reference (detailed in Supplementary figure 1 ). Long- range PCR was performed for the SVA (3.2kb) as previously described1.…”
Section: Methodsmentioning
confidence: 99%
“…Mosaic modifiers, which exist in every patient at variable frequencies, have not been studied extensively. We previously described the presence of somatic mosaicism in XDP with a higher number of repeats detected in the cerebellum and basal ganglia compared to blood 8 . In this present study, we identified novel mosaic repeat motif patterns that deviate from the known hexanucleotide repeat motif and investigate whether they act as new genetic modifiers of repeat instability and AAO of this neurodegenerative disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Control tissues included PFC ( n = 3), MC ( n = 1), CB ( n = 2), AP ( n = 1), caudate nuclei (CN, n = 3) and thalamus (TH, n = 1). Hexamer repeat length for the processed XDP samples was genotyped by Fernandez-Cerado et al 21 and Reyes et al 22 and repeat numbers are as follows: 17.01, 44; 17.06, 41; 17.10, 34; 17.12, 42; 17.13, 46; 17.17, 54; L-7.995, 45; L-10.332, 41.…”
Section: Methodsmentioning
confidence: 99%